Overweight and obesity vs. Metabolic complications In a group of per-sons with intellectual disabilities. Preliminary study - Łopuszańska, Urszula; Skorzyńska-Dziduszko, Katarzyna; Mlak, Radosław; Kryś-Noszczyk, Karolina; Lupa-Zatwarnicka, Krystyna; Makara-Studzińska, Marta (Current Problems of Psychiatry, 2025)
Introduction: Obesity is a major health problem within the population of those with intellectual disabilities. It carries with it a number of negative health consequences that lead to, inter alia, overpressure of the blood, carbohydrate-lipid metabolism disturbances, diabetes type II, cardiovascular disease and stroke. Many forms of obesity in people with mental disabilities are of a genetic background, however, of great importance in its formation is life-style choices and health care system practices. Material and methods: This study included 24 people at 24 to 52 years of age, in whom a diagnosis had been made prior to their attaining 16 years of age, of mild and moderate mental impairment. From these persons, we took venous blood samples (after fasting) in order to obtain data on total cholesterol (TC), HDL cholesterol (HDL), LDL cholesterol (LDL), triglycerides (TG), and glucose (GLUC) levels. Results: Overweight and obesity were diagnosed in 25% of all women and in 25% of all men, whereas obesity was seen in 16% of all women and 23% all men, respectively. A particular problem appeared to be abdominal obesity. This was evident in 41,7% of all surveyed (58,3% of all women and 50% of all men). In addition, hypercholesterolemia was common, and was diagnosed in 75% of all women and 16.7% of all men. This represented 46% of the total surveyed. Conclusions: Our study revealed that environmental factors conducive to mental stimulation, above all, the possibility of em-ployment, foster motor activity. This positively affects the correct metabolic transformation in people with intellectual disabilities.